Establishment of microphone and pistonphone calibration laboratory at Electrical Engineering Faculty, Universiti Teknologi Malaysia - 452878 Ahmad Rafidi Aris
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1998